The In-Vitro Antitumor Effects of AST-3424 Monotherapy and Combination Therapy With Oxaliplatin or 5-Fluorouracil in Primary Liver Cancer - Zhang, Yu; Qin, Shukui; Chao, Jiaojiao; Luo, Yan; Sun, Yandi; Duan, Jianxin (Frontiers in Oncology, 2022)
Primary liver cancer (PLC) is a common and highly lethal malignancy in the world. Approximately 85% of PLC is Hepatocellular carcinoma (HCC), and this study mainly focus on HCC. The onset of liver cancer is insidious, and often complicated with basic liver disease. Meanwhile, its clinical symptoms are atypical, and the degree of malignancy is high. What’s worse is that its treatment is difficult, and the prognosis is poor. All these factors make its mortality close to its incidence. AST-3424 is a prodrug of a potent nitrogen mustard, which targets the tumor by its specific and selective mode of activation and results in the concentration of drug in the tumor and plays a higher intensity of antitumor effect with reduced side effects. The purpose of this study is to explore the antitumor activity and mechanism of AST-3424 monotherapy and in combination with Oxaliplatin (OXA) or 5-Florouracil (5-Fu). Moreover, it can provide experimental basis for further studies. In-vitro studies with AST-3424 in combination with both OXA and 5-Fu has been shown to increase antitumor effect, and the combination with OXA results in a synergistic effect. Together with in vivo results, additional vitro and vivo studies are warranted to furter certify its antitumor effects and explore more potential antitumor mechanisms.